If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 11 = 8x + -5 Reorder the terms: 11 + 3x = 8x + -5 Reorder the terms: 11 + 3x = -5 + 8x Solving 11 + 3x = -5 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 11 + 3x + -8x = -5 + 8x + -8x Combine like terms: 3x + -8x = -5x 11 + -5x = -5 + 8x + -8x Combine like terms: 8x + -8x = 0 11 + -5x = -5 + 0 11 + -5x = -5 Add '-11' to each side of the equation. 11 + -11 + -5x = -5 + -11 Combine like terms: 11 + -11 = 0 0 + -5x = -5 + -11 -5x = -5 + -11 Combine like terms: -5 + -11 = -16 -5x = -16 Divide each side by '-5'. x = 3.2 Simplifying x = 3.2
| 17-20q=4(5q-13) | | 8x+32-6x+4=180 | | 17-20q=4(5q-13)5 | | 3b+4g=12 | | 17-20q=4(-5q-13) | | 0.02n+1=11 | | 7x(2-1)=28 | | 2x^4-9x^2+7=0 | | 3b+4g=12forg | | 2(5-3r)=-4-16 | | -4(r+5)=-73 | | J-6=30 | | 175m-125m+38000=40600-150m | | 30-15b=105 | | 14+25x=35+18x | | 4x^2-36=4(x^2-36) | | (4x-3)(3x-4)=(2x-5)(6x-4) | | 2(5(2)-3)=1(2)+12 | | 8r-11-12r=4+-3r-16 | | 6x-(4-6x)=1.5(8x+12) | | 2x^2-9x^2+7=0 | | 39-8n=-8n(3+4n)+3n | | 6y^4-12xy^5= | | 9(2-a)+4a=3a | | 9x^2-18x-34=6 | | f(x)=((x+4)(x+4))-5(x+4)+9 | | 2(4y+5)+3(4y+1)= | | 7x+4+9x+8=92 | | f(x)=((x+4)(x+4))2-5(x+4)+9 | | 4y+3(y-6)+2=8 | | -3(6-10n)=10(2n-6) | | 28-5x=10+4x |